2020
DOI: 10.1155/2020/5390903
|View full text |Cite
|
Sign up to set email alerts
|

Incidence and Predictors of Maternal and Perinatal Mortality among Women with Severe Maternal Outcomes: A Tanzanian Facility-Based Survey for Improving Maternal and Newborn Care

Abstract: Introduction. Maternal and perinatal mortality is still a major public health challenge in Tanzania, despite the ongoing government efforts to improve maternal and newborn care. Among the contributors to these problems is the high magnitude of severe maternal outcomes (maternal near-miss). The current study, therefore, aimed to identify the magnitude and predictors of maternal and perinatal mortality among women with severe maternal outcomes admitted to Dodoma Regional Referral Hospital. Methods. A retrospecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
13
5

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(19 citation statements)
references
References 38 publications
1
13
5
Order By: Relevance
“…[14][15][16] Tanzania is among countries with high maternal mortality. 1,[17][18][19][20] In 2015 and 2016, 98% of pregnant women receive antenatal care (ANC), although only one in four had the first visit in the first three months of pregnancy. Also, slightly more than half made more than four visits, while the latest recommendation of the WHO is eight visits per pregnancy.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[14][15][16] Tanzania is among countries with high maternal mortality. 1,[17][18][19][20] In 2015 and 2016, 98% of pregnant women receive antenatal care (ANC), although only one in four had the first visit in the first three months of pregnancy. Also, slightly more than half made more than four visits, while the latest recommendation of the WHO is eight visits per pregnancy.…”
Section: Discussionmentioning
confidence: 99%
“…11 Other studies in Tanzania reported a high incidence of the same underlying causes as well. 17,19,30 Severe PPH was the most frequently occurring severe complication in Ndala. In this study, the patients with PPH did fulfill a criterion in the WHO or the SSA -set.…”
Section: Details Of Inclusionsmentioning
confidence: 99%
“…According to WHO estimates, the incidence of preeclampsia in developing countries (2.8% of live births) is seven times higher than in developed countries (0.4% of live births). Eclampsia increases the risk of maternal death both in developed countries (0.4% of live births) and in developing countries (15%) [3][4][5][6][7]. Adequate obstetrical care in developing countries must include clinicians and facilities who are well versed and well prepared to care for preeclamptic and eclamptic patients.…”
Section: Introductionmentioning
confidence: 99%
“…The second stage, the maternal syndrome, results from the failure of cytotrophoblast remodeling of uterine spiral arteries. This cytotrophoblastic failure is thought to release secreted factors that enter the maternal circulation resulting in the signs and symptoms of preeclampsia [7,8].…”
mentioning
confidence: 99%
“…Maternal mortality rate (MMR) in Tanzania is still persistently high. The data from Tanzania has revealed that maternal mortality ratio (MMR) has increased from 454 per 100,000 live births in 2010 to 556 per 100,000 live births by the year 2015 [4]- [7]. Several strategies such as increasing coverage and quality primary health care services for communities in rural and remote areas, timely antenatal care visit, delivery in health facilities and timely postnatal check-up have been adopted by the government in collaboration with the UN agencies and other development partners as a necessary attempt to improve maternal health in the country [5], [8].…”
Section: Introductionmentioning
confidence: 99%